Validation of the Spanish Version of the Parent Diabetes Distress Scale - Marina Beléndez; Lawrence Fisher (Clínica y Salud. Investigación Empírica en Psicología)

(untitled)
Background: Type 1 diabetes is a chronic condition that presents significant challenges not only for affected children and adolescents but also for their parents. The study examined the psychometric properties of the Spanish version of the Parent Diabetes Distress Scale (PDDS-SP) for parents of children and adolescents with type 1 diabetes. Method: Data were collected on 314 parents recruited through diabetes associations and Facebook groups. Participants completed the PDDS-SP, a well-being measure, and provided information about their child’s diabetes and treatment. Results: Exploratory factor analyses identified a 16-item, four-factor structure: parent-child relationship concerns, personal distress, distress about the child’s diabetes self-management, and health care team concerns. Cronbach’s alpha indicated adequate reliability. Higher PDDS-SP scores were associated with lower well-being and more frequent hypoglycemic episodes. Mothers reported higher distress than fathers. Conclusions: The PDDS-SP was found to be a reliable and valid measure for assessing diabetes-related distress among Spanish-speaking parents.